Digital Competence and Influencing Factors Among Elementary Teachers in Zambales: Basis for a Capacity-Building Program - Irene May D. Buenaventura (Future Science / FSH-PH Publications, 2026)
Digital competence is essential for teachers in today’s technology-driven educational landscape. This study assessed the level of digital competence among elementary school teachers in Zone III, Division of Zambales, and examined factors influencing their digital proficiency. Anchored on the DigComp 2.2 Framework, the research focused on six competence areas: professional engagement, digital resources, teaching and learning, assessment, empowering learners, and facilitating learners’ digital competence. A descriptive research design was employed, involving 160 teachers from selected large public elementary schools who responded to a validated and adapted questionnaire. Data were analyzed using frequency, percentage, weighted mean, analysis of variance, and Pearson r correlation. Results revealed that most respondents were female, in middle adulthood, and in the mid-career stage. While teachers demonstrated moderately high levels of self-reported digital competence, findings also showed a statistically significant gap in formal institutional training related to digital integration, indicating reliance on experiential and self-directed learning rather than structured professional development. Significant differences in digital competence were found when respondents were grouped according to age, years of teaching experience, and training exposure. Moreover, moderate relationships existed between digital competence and perceived usefulness, ease of use, availability of infrastructure, and access to digital tools. Based on the findings, an intervention program emphasizing structured training, mentoring, and improved access to digital resources was proposed to support sustained improvement in teaching effectiveness in schools.